A quantitative analysis of two-dimensional manually segmented transrectal ultrasound axial images in planning high dose rate brachytherapy for prostate cancer - Dabić-Stanković, Kata; Rajković, Katarina; Aćimović, Miodrag; Milošević, Nebojša; Stanković, Jovan (Vojnosanitetski pregled, 2017)
Background/Aim. Prostate delineation, pre-planning and catheter implantation procedures, in high-dose rate brachytherapy (HDR-BT), are commonly based on the prostate manually segmented transrectal ultrasound (TRUS) images. The aim of this study was to quantitatively analyze the consistency of prostate capsule delineation, done by a single therapist, prior to each HDR-BT fraction and the changes in the shape of the prostate capsule during HDR-BT, using two dimensional (2D) TRUS axial image. Methods. A group of 16 patients were treated at the Medical System Belgrade Brachytherapy Department with definitive HDR-BT. The total applied median dose of 52 Gy was divided into four individual fractions, each fraction being delivered 2–3 weeks apart. Real time prostate axial visualization and the manual segmentation prior to each fraction were performed using B-K Medical ultrasound. Quantitative analyses, analysis of an area and shape were applied on 2D-TRUS axial images of the prostate. Area analyses were used to calculate the average value of the cross-sectional area of the prostate image. The parameters of the prostate shape, the fractal dimension and the circularity ratio of the prostate capsule contour were estimated at the maximum axial cross section of the prostate image. Results. The sample group consisted of four phases, each phase being performed prior to the first, second, third and fourth HDR-BT fraction, respectively. Statistical analysis showed that during HDR-BT fractions there were no significant differences in the average value of area, as well as in the maximum shape of prostate capsule. Conclusions. Quantitative analysis of TRUS axial prostate segmented images shows a successful capsule delineation in the series of manually segmented TRUS images, and the prostate maximum shape remaining unchanged during HDR-BT fractions.